Uni-2--A dominant mutation affecting leaf development in Phaseolus vulgaris - Garrido, B.; Nodari, R.; Debouck, Daniel G.; Gepts, Paul L. (Oxford University Press, 1991)
Uni-2, a dominant mutation that affects leaf development in Phaseolus vulgaris, is described. The mutant type is characterized by the production of unifoliolate true leaves as opposed to the trifoliolate true leaves that characterize the wild-type phenotype of this species. Segregation data from the F2, F3, and F4 generations of crosses between the unifoliolate mutant and trifoliolate genotypes suggest that the trait is coded by a single dominant gene with some deleteriousness in unifoliolate homozygotes. A new polymorphism for the enzyme methylumbelliferyl esterase was controlled by a single locus (Mue). No linkages were found between the unifoliolate trait and other molecular and morphological markers. (AS)